2011
DOI: 10.14411/eje.2011.081
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly diversity and biogeography on the Croatian karst mountain Biokovo: Vertical distribution and preference for altitude and aspect?

Abstract: Abstract. Geographic isolation, altitude, climate, landscape and habitat are significant predictors of butterfly diversity in mountain ecosystems. Their diversity and its dependence on altitude, aspect (compass bearing) and biogeographic characteristics of the butterflies were surveyed on the karst mountain Biokovo in southern Croatia. The results affirm that there is a high diversity of butterflies in the study area and the species composition and biogeographic elements are more dependent on altitude than asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…On Mt. Biokovo in Croatia, butterfly richness was higher on northern slopes than on the very steep and vegetation-poor southern aspects, which are also more exposed to strong bora winds (Mihoci et al, 2011). Our results did not provide any conclusive evidence on the effects of aspect on butterfly richness, despite the unequal distribution of the aspects in Mt Galičica.…”
Section: Species Richness Patterncontrasting
confidence: 85%
See 3 more Smart Citations
“…On Mt. Biokovo in Croatia, butterfly richness was higher on northern slopes than on the very steep and vegetation-poor southern aspects, which are also more exposed to strong bora winds (Mihoci et al, 2011). Our results did not provide any conclusive evidence on the effects of aspect on butterfly richness, despite the unequal distribution of the aspects in Mt Galičica.…”
Section: Species Richness Patterncontrasting
confidence: 85%
“…However, a bimodal pattern is not a rare phenomenon for butterflies peaking at midaltitudes and it has often been recorded in other studies (Gutierrez and Menendez, 1995;Levanoni et al, 2011;Stefanescu et al, 2011, Gallou et al, 2017. There is also considerable evidence for the monotonic decline in butterfly diversity along the elevation gradient (Mihoci et al, 2011;Leingärtner et al, 2014;Kaltsas et al, 2018), but an insignificant trend (Kaltsas et al, 2018) and increase in species richness (Wettstein and Schmid, 1999;Pyrcz et al, 2009) has also been reported. Note that the increase in species richness with altitude is more likely to be caused by specific habitat composition (Wettstein and Schmid, 1999) or by the study of an exclusively montane taxonomic group (Pyrcz et al, 2009).…”
Section: Species Richness Patternmentioning
confidence: 68%
See 2 more Smart Citations
“…Despite the aforementioned low species richness at mid‐elevations on Olympus, it is very interesting that the butterfly communities at the ALT3 zone showed a variant and intermediate character, sharing similarities with assemblages at both lower and higher altitudes, whereas retaining their own faunal character with Pieris rapae as their most distinctive species. The altitudinal zonation of butterflies is quite common (Debinsky & Brussard, ; Gutiérrez, ; Fleishman et al ., ; Mihoci et al ., ) and has been related to habitat, host‐plant dependence and climatic tolerance, which affect the distribution of butterfly species (Gutiérrez & Menéndez, ; Wettstein & Schmid, ; Pyrcz & Wojtusiak, ; Storch et al ., ). In our case, the altitudinal zonation of butterfly communities at the two NATURA 2000 sites was mainly caused by the specificity of three red‐listed species for high altitudes ( E. melas , E. oeme and P. dorylas ), a fact that stresses the conservation priority of the ALT4 and ALT5 zones, especially regarding butterflies that are known to be highly sensitive to climate change (Parmesan et al ., ; Devictor et al ., ; van Swaay et al ., ).…”
Section: Discussionmentioning
confidence: 99%